Integrative Behavioral Couple Therapy: Theoretical Background, Empirical Research, and Dissemination. Issue 3 (26th May 2016) - Roddy, McKenzie K.; Nowlan, Kathryn M.; Doss, Brian D.; Christensen, Andrew
Abstract : Integrative Behavioral Couple Therapy (IBCT), developed by Drs. Andrew Christensen and Neil Jacobson, builds off the tradition of behavioral couple therapy by including acceptance strategies as key components of treatment. Results from a large randomized clinical trial of IBCT indicate that it yields large and significant gains in relationship satisfaction. Furthermore, these benefits have been shown to persist for at least 5 years after treatment for the average couple. Not only does IBCT positively impact relationship constructs such as satisfaction and communication, but the benefits of therapy extend to individual, co‐parenting, and child functioning. Moreover, IBCT has been shown to operate through the putative mechanisms of improvements in emotional acceptance, behavior change, and communication. IBCT was chosen for nationwide training and dissemination through the Veteran Affairs Medical Centers. Furthermore, the principles of IBCT have been translated into a web‐based intervention for distressed couples, OurRelationship.com . IBCT is continuing to evolve and grow as research and technologies allow for continued evaluation and dissemination of this well‐supported theoretical model.